2020
DOI: 10.1126/science.aba1135
|View full text |Cite
|
Sign up to set email alerts
|

A parapithecid stem anthropoid of African origin in the Paleogene of South America

Abstract: Phylogenetic evidence suggests that platyrrhine (or New World) monkeys and caviomorph rodents of the Western Hemisphere derive from source groups from the Eocene of Afro-Arabia, a landmass that was ~1500 to 2000 kilometers east of South America during the late Paleogene. Here, we report evidence for a third mammalian lineage of African origin in the Paleogene of South America—a newly discovered genus and species of parapithecid anthropoid primate from Santa Rosa in Amazonian Perú. Bayesian clock–based phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 29 publications
2
82
0
Order By: Relevance
“…In the same publication, Stirton (1951) exceptional record, however, is unique, and represents only a snapshot of the evolutionary history of New World monkeys. Although the primate fossil record has continued to improve (slowly but considerably) in South America (e.g., Fleagle and Bown, 1983;Fleagle et al, 1987;Fleagle, 1990;Flynn et al, 1995;Kay et al, 1998Kay et al, , 2008Kay et al, , 2019Takai et al, 2000;Tejedor et al, 2005Tejedor et al, , 2006Kay and Cozzuol, 2006;Kay, 2010;Kramarz et al, 2012;Marivaux et al, 2012Marivaux et al, , 2016aPerry et al, 2014;Bond et al, 2015;Novo and Fleagle, 2015;Antoine et al, 2016;Bloch et al, 2016;Novo et al, 2018;Seiffert et al, 2020), virtually none of the species and genera recorded at La Venta had so far been found elsewhere. Only one lower molar recovered in much more recent levels (Huayquerian SALMA) in Acre, Brazil, was tentatively assigned to the alouattine Stirtonia known in La Venta (Kay and Frailey, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same publication, Stirton (1951) exceptional record, however, is unique, and represents only a snapshot of the evolutionary history of New World monkeys. Although the primate fossil record has continued to improve (slowly but considerably) in South America (e.g., Fleagle and Bown, 1983;Fleagle et al, 1987;Fleagle, 1990;Flynn et al, 1995;Kay et al, 1998Kay et al, , 2008Kay et al, , 2019Takai et al, 2000;Tejedor et al, 2005Tejedor et al, , 2006Kay and Cozzuol, 2006;Kay, 2010;Kramarz et al, 2012;Marivaux et al, 2012Marivaux et al, , 2016aPerry et al, 2014;Bond et al, 2015;Novo and Fleagle, 2015;Antoine et al, 2016;Bloch et al, 2016;Novo et al, 2018;Seiffert et al, 2020), virtually none of the species and genera recorded at La Venta had so far been found elsewhere. Only one lower molar recovered in much more recent levels (Huayquerian SALMA) in Acre, Brazil, was tentatively assigned to the alouattine Stirtonia known in La Venta (Kay and Frailey, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recent field efforts in Peruvian Amazonia have proven that the Andean foothills had great paleontological potential for highlighting the evolutionary history of New World monkeys. Although very fragmentary, the paleontological evidence recently gathered in this area of Western Amazonia has shed new light on the origin, emergence, and subsequent evolution of platyrrhines (Marivaux et al, 2012(Marivaux et al, , 2016aBond et al, 2015;Kay et al, 2019;Seiffert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that the ancestors of the Platyrrhini migrated to South America either on a raft of vegetation or via a land bridge ( Beard, 2004 ). Two possible rafting routes have been suggested, either across the Atlantic Ocean from Africa (then the Afro-Arabian plate; Godinot, 2020 ; Seiffert et al, 2020 ) or across the Caribbean from North America. The former would have the New World monkey ancestors sail on the south equatorial paleo current (SEC), 35–32 mya during the Oligocene ( Godinot, 2020 ).…”
Section: Primate Origins Evolution and Migrationsmentioning
confidence: 99%
“…This is sustained by a large number of taxa shared between Africa and South America, but also with other landmasses and especially India, including hystricognath rodents, anthropoid monkeys, afrotherian mammals, pipid frogs, freshwater fishes (cichlids and aplocheiloids), birds (parrots, hoatzins, phororhacoids), and lizards (geckos), and Malpighiaceae, Asteraceae, and Bromeliaceae among plants 52,[54][55][56][57][58][59] . Further support for this interchange includes the finding of several lineages of metatherians, anthropoid monkeys and hystricognath rodents in South America, indicating multiple dispersals between South America and Africa and vice-versa during the Paleogene [60][61][62][63][64] . As enumerated above, the evidence indicating a fluid interchange between South America and other Southern Hemisphere landmasses and India has been greatly increasing during the last years (see below).…”
Section: Litoptern Affinities and The Splendid Isolation Of South Amementioning
confidence: 94%